Preparation of Cu2O Superhydrophobic Film with Hierarchical Structure via the Facile Route - Pei1, Mingde; Wang1, Bo; Tang1, Yunhui; Zhang1, Xuehong; Yan1, Hui; Zhang2, Xiaoxue (Asian Journal of Chemistry, 2014)
A Cu2O layer was employed as a new method to achieve the superhydrophobicity on a copper surface using a simple hydrothermal method. First, a Cu2O layer with a hierarchical structure was grown on the copper surface using an oxidization step and it exhibited the hydrophilicity. The analysis results of XRD and XPS confirmed the formation of a Cu2O phase on the copper surface. Second, the Cu2O surface was changed to superhydrophobicity via a modifying process using 1H,1H,2H,2H-perfluorodecyltriethoxysilane. Peaks corresponding to F1s, -CH2, -CF2 and -CF3 groups in the XPS spectra confirm the assemblage of the F-contained radicals on the surface. The wetting mechanism is discussed briefly. Wetting tests also demonstrate that a water droplet on the surface can slide away very easily, even with only a slight tilt and that it has a lower adhesion to the modified surface.